PEMANENAN AIR HUJAN BERBASIS ROOFTOP UNTUK REDUKSI BANJIR DAN BUDIDAYA IKAN NILA SISTEM RAS DI SDN LEUWI BANDUNG 1 - Suprapti, Suprapti; Fitriani, Eka Nur; Marlapa, Eri; Rahman, Abdul (Jurnal Abdi Insani, 2025)
The Community Service Program (PKM) focuses on empowering school groups with SDN Leuwi Bandung 1 as its partner, located at Jl. Gunadi No. 28, RT/RW: 7/3, Citeureup, Dayeuhkolot, Bandung, West Java. The main objective of the PKM program is to implement rooftop-based rainwater harvesting technology to reduce flooding. The harvested rainwater is then filtered to be used as water for Nila fish cultivation. The result of Nila fish cultivation is expected to increase protein consumption and increase the income of teachers' families. Partner problems include frequent flooding, the income of honorary teachers and school guards is still relatively very low. The PKM implementation method includes discussion and socialization of the PKM program to school partners, explanation and application of rooftop-based rainwater harvesting technology, training and implementation of Nila fish cultivation using the RAS (Recirculating Aquaculture System) system, financial management and marketing training, handover of inventory assets funded by the Ministry of Education and Technology for the 2025 fiscal year and mentoring to school partners. The PKM will be implemented from June to December 2025. Results indicate that partners have the skills and can practice rooftop-based rainwater harvesting and RAS fish cultivation, as well as financial and marketing management. This program aims to improve partners' abilities and skills in increasing family income and fostering greater independence and prosperity. Furthermore, these activities can be expanded to the homes of each partner school, leading to community economic independence.